OPTIMALISASI PERFORMANCE REPRODUKSI DAN ADOPSI INOVASI UREA MOLASES BLOCK (UMB) PADA KELOMPOK PETERNAKAN SAPI MAKMUR, KECAMATAN PAUH, PADANG - Ediset Ediset; Rusmana Rusmana; Edwin Heriyanto; Amrizal Anas; Basril Basyar (Jurnal Hilirisasi IPTEKS, 2018)
The purpose of this activity is to: 1) increase knowledge and skills of breeders on reproduction performance, and 2) to increase knowledge and skills of farmers in making Urea Molases Block (UMB) feed, and 3) to grow entrepreneurship spirit in the field of animal husbandry cow. The goal of community service activities is the members of the Makmur cattle breeder group and other breeders who are not members of the group and Agricultural Extension workers who have a working area in the location of devotional activities. The method applied in this devotional activity is the method of counselling with several approaches, namely lecture / socialisation method, home visit and farming and demonstration methods. The lecture / socialisation approach is used at the time of delivery of materials related to entrepreneurial spirit, and the home visit approach is done to deliver materials related to reproductive performance, while the demonstration extension approach is applied to the introduction of Urea Molases Block (UMB) feed innovation. The result of the community service activity shows that the participation of the target of the activity of high service to the activity done by the team of dedication because besides the group members who attended also present other breeders, extension workers and even farm students who are doing Farm Experience, as well as on the discussion session many questions appear related to the material presented by the resource person and even on some aspects of the discussion are quite deep. The description of the participation of the activity is in line with the behaviour change that occurs on the target of the activity, especially the change in the cognitive aspect and the change in the psycomotoric aspect, where in the aspect cognitive the breeder knows the economic potential of the cattle breeding business and knows and skilfully arranges the reproduction of livestock especially after the mother gives birth to the child, skilled way of making UMB and how to give UMB to cattle raised.